2023
DOI: 10.3390/nu15061322
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Key Constituents in Cichorium intybus L.

Abstract: The genus Cichorium (Asteraceae) that originates from the Mediterranean area consists of six species (Cichorium intybus, Cichorium frisee, Cichorium endivia, Cichorium grouse, Cichorium chico and Cichorium pumilum). Cichorium intybus L., commonly known as chicory, has a rich history of being known as a medicinal plant and coffee substitute. A variety of key constituents in chicory play important roles as antioxidant agents. The herb is also used as a forage plant for animals. This review highlights the bioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 118 publications
2
4
0
Order By: Relevance
“…[27] Furthermore, it was postulated that α-LA could play a pivotal role in improving the concurrent challenges of diabetes-associated nephropathy and hyperglycemia in STZ-induced diabetic rats. [28] Our findings are in alignment with contemporary research highlighting the antioxidant capabilities of bioactive plant components and their potential to alleviate oxidative stress stemming from hyperglycemia. [29] T A B L E 1 Biochemical estimations, body weight, and blood glucose in different groups.…”
Section: Discussionsupporting
confidence: 83%
“…[27] Furthermore, it was postulated that α-LA could play a pivotal role in improving the concurrent challenges of diabetes-associated nephropathy and hyperglycemia in STZ-induced diabetic rats. [28] Our findings are in alignment with contemporary research highlighting the antioxidant capabilities of bioactive plant components and their potential to alleviate oxidative stress stemming from hyperglycemia. [29] T A B L E 1 Biochemical estimations, body weight, and blood glucose in different groups.…”
Section: Discussionsupporting
confidence: 83%
“…The present study showed that CA also alleviated Aβ pathology and improved the expression of synaptic-function-related markers via L1. It is noted that some active substances in traditional Chinese herbs, such as chlorogenic acid and ursolic acid, have similar roles to CA in the treatment of neurodegenerative disease [ 32 , 33 ]. Chlorogenic acid improved mitochondrial dysfunction and protected against neuronal cell death in a PD mouse model [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the administration of chicory could improve oxidative stress and promote the protection of chicory against atherosclerosis. 112,113…”
Section: Pharmacological Activitymentioning
confidence: 99%